The Impact of Shifting to Distance Education in Light of the Coronavirus Crisis from the Perspective of Faculty Members at King Saud University - Alenazi, Hayfa Ali (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the transition to distance education for King Saud University students in light of the coronavirus crisis from the faculty members’ perspective following certain variables; such as obtaining the perspective of faculty members about students’ use of distance education tools, their satisfaction level with the transition toward distance education, and the reflection of such transition and its obstacles in light of the coronavirus crisis. The study followed the descriptive approach with a sample of (362) faculty members at King Saud University. The study used a questionnaire consisting of (4) axes that were directly related to the study questions. The results of the study indicated that the application level of distance education tools by King Saud University students in light of the coronavirus crisis came largely according to the relative weight of 81.7%. There was a significant level of satisfaction with King Saud University students regarding the transition, with a relative weight of 80.9%. The study also showed that there were significant repercussions regarding the transition to distance education in light of the coronavirus crisis; where the approval rate was 86.6%. In addition, there were noticeable obstacles, from the perspective of the university’s faculty members that hinder the transition process for the students; where the rate was 72.3%. The results showed that there were statistically significant differences between the responses of the study sample towards the impact of shifting to distance education due to the age variable to the benefit of the sample individuals under the age of (40); no such differences appeared on the variable of gender. The study showed the presence of statistically significant differences between the responses of the study sample towards the impact of shifting to distance education due to the variable of years of experience; these differences were for the benefit of those who have less than (5) years of years’ experience and for the benefit of the sample who have (5) to (10) years of experience. The researcher recommended the necessity of spreading awareness in the local community and changing their views towards graduates and students of distance education by believing in them with confidence and conviction in their capabilities and competence.